O cell, where art thou?: the mechanisms of shoot meristem patterning - Gaillochet, Christophe; Daum, Gabor; Lohmann, Jan U. (Current opinion in plant biology, 2015)
Plants develop postembryonically from pools of continuously active stem cells embedded in specialized tissues called meristems, which are located at the growing points of shoot and root. How these stem cells are established, maintained and guided towards differentiation within the highly dynamic shoot apical meristem is only beginning to emerge. At the core of the complex regulatory system are spatially distinct subdomains within the shoot apex, in which cells carry out defined functions, despite highly similar phenotypes. Spatial and temporal control of these domains appears to rely on an elaborate network of phytohormone signaling, transcriptional loops and intercellular trafficking of key regulators. In this review, we aim at summarizing and connecting the mechanisms underlying the spatial organization of the shoot apical meristem and the sequence of molecular events occurring during the life of a shoot cell, from its birth towards its differentiation.
Available online 25 November 2014
Gesehen am 19.06.2017